Diverse Voices of Disabled Sexualities in the Global South - Chappell, Paul; de Beer, Marlene (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This volume aims to critically engage with constructs and experiences of disabled sexualities through Africa, Asia, Latin America and the Caribbean. In doing so, it is hoped that the questions raised, relfections, analyses and arguments will provide readers with a catalyst through which to (re)think disabled sexualities from the perspective of the Global South. What makes this edited volume unique is besides chapters from emerging academics and disability activists who either live or work in the Global South, it also includes personal contributions from disabled people across the Global South. This volume takes a broad perspective on disabled sexualities addressing such areas as gender, race, culture, colonialism, body image, sexual pleasure, sexuality education, sexual access, sexual and reproductive health services, queer sexualities, and sexual rights and justice. The volume will be of interest to international and national organisations for people with disabilities, gender and sexuality researchers, health professionals, social workers, academics and students at all higher education and training institutions interested in disability, gender queer and sexuality studies.